Rural Welfare in China - Pan, Yi (Springer International Publishing : Imprint: Springer, 2017)
This comprehensive reference views China's welfare system through a cultural-historical lens to integrate its complex story into the global study of welfare. Focusing on the mainland's vast, mainly rural population and its long and complicated history, it analyzes rural welfare from the imperial dynasties, to the socialist planned economy under Mao Zedong, to its recent history in the current market economy. Findings from government and academics explore salient topics such as urban/rural inequity, the situation of migrant workers, change of social security system, the community development of the countryside, and the relationships of rural welfare policy with social structure, cultural background, economic development and political institution. This broad and deep knowledge gives readers the tools necessary for understanding the relationship of China's unique and nuanced past to its prominent status in the evolving global economy. Among the book's topics: Welfare studies in the West and China Welfare practice in the period of 1840-1949 Creation of the Socialist Welfare System: socialist reformation and construction The Social Security system in rural China, 1979-1998 Re-collectivized process in welfare and economy Welfare's political contexts: rural grass-roots democracy With its accessible, up-to-date coverage and holistic approach to its subject, Rural Welfare in China will find a diverse interested audience, including sociologists, political economists, and social policymakers. .
Keywords: Social sciences.; Political economy.; Economic policy.; elektronické knihy; electronic books